Serum Cystatin C as a Biomarker of Cardiac Diastolic Dysfunction in Patients With Cardiac Disease and Preserved Ejection Fraction. Issue 4 (1st August 2013) - Nosaka, Kazumasa; Nakamura, Kazufumi; Kusano, Kengo; Toh, Norihisa; Tada, Takeshi; Miyoshi, Toru; Doi, Masayuki; Kohno, Kunihisa; Morita, Hiroshi; Ito, Hiroshi
Abstract : Diastolic dysfunction of the heart is correlated with cardiac mortality. Serum cystatin C (CysC) is an endogenous marker of kidney function. It is not clear whether serum CysC is associated with diastolic dysfunction in patients with varying cardiac conditions with concomitant diastolic abnormalities and preserved ejection fraction (EF). The authors measured serum CysC levels in patients with cardiac diseases and examined the relationships between serum CysC levels and diastolic function. Serum CysC was measured and echocardiography was performed in 124 consecutive patients with cardiac diseases. Transmitral flow (TMF) patterns surrogating diastolic function were categorized into two groups: a normal group and an abnormal group. Serum CysC and BNP showed a significant positive correlation. There were no significant differences in serum CysC among those cardiac diseases. Seventy‐eight patients with cardiac disease and preserved EF (left ventricular EF ≥50%) and without renal dysfunction (estimated glomerular filtration rate ≥60 mL/minute/1.73 m 2 ) were examined. Multivariate linear regression analysis demonstrated that left atrium diameter and abnormal TMF patterns were independent determinants of serum CysC. Furthermore, patients with elevated serum CysC levels had poor prognosis. Serum CysC is associated with diastolic dysfunction in patients with various cardiac diseases and preserved EF. Serum CysC might be a biomarker of cardiac diastolic dysfunction in patients with preserved EF.